Karakteristik Fisik, Kimia dan Mutu Sensori Susu Bubuk Kecambah Kedelai Instan Berdasarkan Variasi Penambahan Maltodekstrin - Rosita Dewi; Siti Aminah; Agus Suyanto (Jurnal Pangan dan Gizi, 2019)
The addition of maltodextrin is known to coat flavor components, increase volume, accelerate the drying process, prevent heat damage and increase solubility and characteristic quality of sensory. The general purpose of the research is to know the effect of variation of maltodextrin addition to physical characteristics (white degree, solubility and water absorption), chemistry (water content, ash content, fat content, protein and carbohydrate) and sensory milk quality of instant soybean sprouts based on variation of maltodextrin addition. The method of this research is monofactorial experiment, which consists of 5 treatment of maltodextrin concentration, 0%, 5%, 10%, 15% and 20%. Each treatment was repeated 5 times, so that 25 experimental units were obtained. Physical and chemical test results were analyzed using Anova method followed by Duncan's advanced test while the sensory quality test data were analyzed using Friedman followed by Wilcoxon's advanced test. The results showed that there was a significant effect of the addition of maltodextrin concentration to physical test (white degree, solubility and water absorption) and water content, crude fiber, protein and carbohydrate but no significant effect on ash and fat content. Instant soybean sprouts with a 15-20% maltodextrin variation yield the best physical, chemical and sensory quality.